2008
DOI: 10.1089/rej.2007.0627
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Genes and Genetic Interrelationships Underlying the Impact of Calorie Restriction on Maximum Lifespan: An Artificial Intelligence-Based Approach

Abstract: Novel artificial intelligence methodologies were applied to analyze gene expression microarray data gathered from mice under a calorie restriction (CR) regimen. The data were gathered from three previously published mouse studies; these datasets were merged together into a single composite dataset for the purpose of conducting a broader-based analysis. The result was a list of genes that are important for the impact of CR on lifespan, not necessarily in terms of their individual actions but in terms of their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Similarly, Drosophila MRPL12 is required for cyclin-dependent growth signaling (34). Last, an in silico study identified MRPL12 as one of a small set of interacting genes that might be responsible for the longevity-promoting effects of caloric restriction (35). We speculate that the dynamic nature of the two forms of MRPL12 and the instability of POLRMT when MRPL12 levels are perturbed might contribute to these unique properties.…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, Drosophila MRPL12 is required for cyclin-dependent growth signaling (34). Last, an in silico study identified MRPL12 as one of a small set of interacting genes that might be responsible for the longevity-promoting effects of caloric restriction (35). We speculate that the dynamic nature of the two forms of MRPL12 and the instability of POLRMT when MRPL12 levels are perturbed might contribute to these unique properties.…”
Section: Discussionmentioning
confidence: 85%
“…Employing the 400 nM concentration of level of GIT2 siRNA to reduce cellular GIT2 levels, we were able to recapitulate selected expression data generated from our microarray analysis, with specific relevance to beta cell function, metabolism, diabetes, and aging (Table S15 in Supplementary Material: Figures 8 B–I). Hence acute siRNA; mediated reduction of cellular GIT2 caused increased expression of Dcx [doublecortin, Figure 8 C ( 88 )], Glo1 [glyoxylase I, Figure 8 D ( 89 )], Ndufb10 [NADH dehydrogenase (ubiquinone) 1 beta subcomplex subunit 10, Figure 8 E ( 90 )) as well as a decreased expression of Mrpl12 [mitochondrial ribosomal protein L12, Figure 8 F ( 91 )], Atm [ataxia telangiectasia mutated, Figure 8 G ( 18 )], Reg3b [regenerating islet-derived 3 beta, Figure 8 H ( 92 )], and Sesn1 [sestrin 1, Figure 8 I ( 93 )].…”
Section: Resultsmentioning
confidence: 99%
“…MRPL12 is the first mitochondrial ribosomal protein to be characterized in mammals ( Frei et al., 2005 ), and its mutations lead to growth retardation, neurological deterioration, and mitochondrial translation deficiency ( Serre et al., 2013 ). In addition, an artificial intelligence analysis showed that MRPL12 plays central roles regarding the effects of calorie restriction on life extension ( An et al., 2008 ). And MRPL12 was identified as one of the significant down-regulation mitochondrial proteins in prenatal stress-related mitochondrial biogenesis in the frontal cortex and hippocampus ( Olszanecki and Basta-kaim, 2015 ).…”
Section: Discussionmentioning
confidence: 99%